Peran Taman Bacaan Masyarakat Samera Indonesia dalam Meningkatkan Literasi Kelompok Belajar Desa Tuntungan I, Kecamatan Pancur Batu, Kabupaten Deli Serdang, Sumatera Utara - Putri Ardina; Hasan Sazali (Universitas Sebelas Maret Library, 2025)
This study aims to examine the strategic role of Taman Bacaan Masyarakat (TBM) Samera Indonesia in improving the literacy of study group children aged 8–12 years in Desa Tuntungan I, Kecamatan Pancur Batu, Kabupaten Deli Serdang, Sumatera Utara. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation. The findings show that the TBM does not merely provide access to reading materials but also functions as a social learning space that fosters critical thinking, communication, and information processing skills. Activities such as shared reading, book discussions, and basic literacy training support the four key pillars of information literacy: recognizing information needs, seeking, using, and evaluating information independently. This approach aligns with the Seven Faces of Information Literacy framework and the concept of literacy as a social practice. Despite challenges such as limited facilities and low parental involvement, TBM Samera Indonesia has proven effective in building a community-based literacy culture. The study recommends cross-sectoral support to strengthen institutional capacity and ensure the sustainability of literacy programs responsive to local needs.